2021
DOI: 10.1002/pa.2780
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between political relations with audit quality and auditor industry expertise

Abstract: The present study assesses the relationship between political relations, audit quality, and auditor industry expertise. In other words, this paper attempts to answer the question of “whether the political relations can enhance the audit quality and auditor industry expertise or not.” For this study, the multivariate regression model is used for hypothesis testing. Using the multivariate regression model, research hypotheses were also tested using a sample of 768 year‐firm listed on the Tehran Stock Exchange du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…This result aligns with evidence from Iran, which was investigated by Khaksar et al. (2021b), confirming that countries with high political involvement in an industry experience more competition in auditing but the quality of audits is poorer (audit fee in the present study).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This result aligns with evidence from Iran, which was investigated by Khaksar et al. (2021b), confirming that countries with high political involvement in an industry experience more competition in auditing but the quality of audits is poorer (audit fee in the present study).…”
Section: Resultssupporting
confidence: 91%
“…Fee discounts boost audit company rivalry (Abdullatif and AlRahahleh, 2020). This is typical for most developing countries, as shown in the analysis conducted by Khaksar et al (2021b). By utilizing data from Iran, they demonstrated that businesses with tight political ties boost audit market competition but reduce quality and integrity.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 78%
See 2 more Smart Citations
“…Based on Audousset-Coulier et al's (2016) analysis on the validity of the measures of IS in empirical research, audit fee-based measures are rarely used in the auditing literature as a proxy to measure auditor expertise due to the lack of audit fees disclosures. Nonetheless, audit fee-based metrics are the favoured measure proxy for industry specialist measures than the other proxies used in previous literature because audit fees accurately reflect audit work; thus, audit fees are seen as a consequence of the customer's size, sophistication and risks (Khaksar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%